Media Pembelajaran Silsilah Marga Adat Batak Toba Berbasis Animasi Menggunakan Adobe Flash - Rini Rahmadani Sinambela; Herlina Harahap; Mufida Khairani (LKP Unity Academy, 2023)
Genealogy or commonly called Tarombo by Batak people is a lineage that has become customary for people to know genealogy or kinship relationships. . However, this custom has begun to disappear from the Batak people because of the hard-to-find family data, the expanding genealogy, and the few people who know the genealogy. The lineage is called Tarombo. These things make Tarombo lose its appeal and become the background of this research. The purpose of this study is to build an application system that will become a medium for users, especially the Toba Batak ethnicity, to be able to have, create or continue family genealogies and make it easier for us to find genealogies or Tarombo clans and families. This application is designed using Adobe Flash CS6 which has a pretty good performance. The system development method used in system development is the literature study method, which collects supporting data related to research such as from social media, websites or other sources. Based on the test results, the genealogy application is running successfully on the Windows 10 operating system. This study resulted in an application with the main function as a medium that requires information about the genealogy of the Batak clan, especially the Sinambela clan and provides the desired convenience and speed.